Peran Pest Control Dalam Meningkatkan Kebersihan di Khas Hotel Makassar - Ab., Ahmad; Jaya, Risman; Ningsi, Gustia (Journal of Hospitality Accommodation Management (JHAM), 2024)
Hotels must always be kept clean to avoid pest attacks that can interfere with guest comfort during their stay. This study aims to determine the handling of pest control at Hotel Khas Makassar. The method used in this research is a qualitative approach using qualitative descriptive analysis through observations and interviews with pest control officers who carry out pest control. The results showed that pest control handling at Hotel Khas Makassar has been running well, this is because the hotel involving an effective monitoring system and cooperation with pest control providers.